Gambaran Suhu Dan Lama Proses Penyembuhan Luka Diabetes Di Rumah Luka Surabaya - Ermalynda Sukmawati; Agustina Chriswinda Bura Mare (JURNAL NERS LENTERA, 2023)
Diabetic ulcers are one of the causes that occur due to patients suffering from diabetes due to increasing age, overweight, and lifestyle. Physiologically, the body can repair damage that occurs in skin tissue which is called wound healing. The process of cell repair in wound healing is very dependent on the depth of the wound that occurs in the skin. One way to find out the healing process of diabetic wounds is to check the temperature and duration of the wound. Purpose: This study aims to determine the effect of temperature and wound duration on the wound healing process in diabetic wounds at the Wound Hospital in Surabaya. Research Method: This research uses descriptive research. The population used in this study were wound care patients at Surabaya Wound Hospital in June 2023. The sampling technique used was accidental sampling with a total sample of 36 respondents. The study conducted interviews and measured wound temperature using a thermo gun. Results: Most of the respondents were male, namely 19 people (52.8%) and the final elderly respondents, namely 13 people (36.1%). The average wound temperature is 34.58°C. The mean wound length was 8.06 months. Conclusion: Skin that has been injured or injured can affect wound temperature and wound healing time in diabetic wounds, especially in respondents who have diabetic wounds with complications.